2022
DOI: 10.1177/00938548221104980
|View full text |Cite
|
Sign up to set email alerts
|

Work in Long-Term Restrictive Housing and Prison Personnel Perceptions of the Humanity of People Who Are Incarcerated

Abstract: The punitive era in the United States and other countries has included reliance on long-term restrictive housing (LTRH)—consisting of solitary confinement with few privileges—as a means of managing violent and disruptive individuals in prison. We examine how work in such housing may influence how personnel, including officers and staff, view individuals in prison and assess two hypotheses. First, those who work in LTRH will be more likely to hold a dehumanized view of these individuals. Second, the theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Extending theories of dehumanization to solitary confinement research will require development of more reliable measures to assess the various ways through dehumanization manifests among incarcerated people and correctional staff who work in these spaces. Insights into the experiences of correctional staff working in solitary confinement units may shed light onto how carceral policies governing their profession may result in harms and behaviors that do not align with their intentions as individuals ( Mears et al, 2022 ). Our study was also unable to account for the possibility that people in the sample had endured solitary confinement in other carceral settings outside of Louisiana or in parish jails, which plausibly could bias our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Extending theories of dehumanization to solitary confinement research will require development of more reliable measures to assess the various ways through dehumanization manifests among incarcerated people and correctional staff who work in these spaces. Insights into the experiences of correctional staff working in solitary confinement units may shed light onto how carceral policies governing their profession may result in harms and behaviors that do not align with their intentions as individuals ( Mears et al, 2022 ). Our study was also unable to account for the possibility that people in the sample had endured solitary confinement in other carceral settings outside of Louisiana or in parish jails, which plausibly could bias our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Mears et al. (2022) suggested that exposure to harsh carceral settings leads officers to dehumanize incarcerated people. This article builds on these findings, but it also highlights the key role broader organizational frameworks play in shaping CO use of force.…”
Section: Discussion Areas For Future Research and Limitationsmentioning
confidence: 99%
“…These structures spurred use‐of‐force decisions, but the same factors that created this blind spot also created limits on what actions officers could justify, necessitating construction and outsourcing to create plausible deniability. When presented with moments where force was an option, my participants relied on occupational cultures to recognize the opportunity (Higgins et al., 2022; Mears et al., 2022), but they ended up making the decision based on whether the opportunity was “smart” with relation to broader organizational frameworks.…”
Section: Discussion Areas For Future Research and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some argue it is a form of cruel and unusual punishment that causes harm (Fellner & Mariner, 1997). Others posit that it is an effective management strategy that keeps the prison population safe by deterring and incapacitating problematic individuals (Mears et al, 2020). This debate has resulted in an increase in scholarly interest in the effect of RH placement on correctional institutions, the psychological well-being of individuals serving time in RH, and their post-release behaviors.…”
Section: Introductionmentioning
confidence: 99%